Gut capacity of broiler breeder hens - Nascimento, M. Q. [UNESP]; Gous, R. M.; Reis, M. P. [UNESP]; Viana, G. S.; Nogueira, B. R. F. [UNESP]; Sakomura, NK. [UNESP] (Taylor & Francis Ltd, 2021)
1. Broiler breeders are subjected to qualitative or quantitative feed restrictions to prevent obesity, which causes major health and welfare problems. Diluting their feed by adding inert or low nutrient, bulky materials can reduce obesity, but the capacity of the gut needs to be determined to apply this strategy successfully. Two trials were conducted to measure the bulk capacity of Ross 308 broiler breeders prior to and after the onset of lay. The trial was completely randomised, with nine individually-caged breeders, with each cage as a replicate, totalling 189 birds per trial 2. Birds were given ad libitum access to one of 21 maize-soyabean based feeds, an undiluted control or progressive dilution (10, 20, 30 and 40%) with either cellulose fibre, rice husk, sand, vermiculite or sawdust. Feeds were analysed for density, crude-, acid detergent- and neutral detergent-fibre, water-holding capacity (WHC), cation-exchange capacity and oil-holding capacity. 2. In general, feed intake (scaled to body weight(0.67)) increased and then declined as the proportion of each diluent increased. Intake increased linearly when rice hulls and sand were used as diluents. 3. Water holding capacity was the most appropriate measure to define the gut capacity of broiler breeders. 4. The trial data was used to estimate the maximum-scaled feed intake (SFImax) in broiler breeders, which was 240-56.1WHC + 4.34WHC(2) g/kg(0.67)/d.
Keywords: Bulk capacity; diluted feed; gastrointestinal tract; physical characteristics; voluntary feed intake